Adverse Events Associated with Intranasal Sprays: An Analysis of the Food and Drug Administration Database and Literature Review. (November 2021) - Ahsanuddin, Salma; Povolotskiy, Roman; Tayyab, Rahma; Nasser, Wissam; Barinsky, Gregory L.; Grube, Jordon G.; Paskhover, Boris
Background: Intranasal sprays (INSs) are commonly used medications for the treatment of many rhinologic conditions. Despite their popularity, an analysis of a nationwide reporting database and comparison to the available literature has never been performed. Methods: The Food and Drug Administration Adverse Event Reporting System (FAERS) database was accessed to obtain adverse event (AE) records from 2014 to 2019 for varying INSs, including: 10 corticosteroids, 1 alpha adrenergic, and 3 antihistamines. The Proportional Reporting Ratios (PRR) and Reporting Odds Ratios (ROR) were calculated for dyspnea, anosmia, ageusia/dysgeusia, epistaxis, and headache. A PRR ≥ 2 or ROR ≥ 1 was considered significant. Results: Corticosteroids had 98 864 total reported AEs to the database, followed by antihistamines (7011) and alpha adrenergics (2071). In total, dyspnea was reported 5843 times, followed by headache (4230), epistaxis (1205), ageusia/dysgeusia (920), and anosmia (312). Overall, PRR and ROR values for dyspnea ranged from 0.51 to 4.25 and 0.51 to 4.49; for dysgeusia/ageusia from 0.56 to 6.09 and 0.56 to 6.12; and for epistaxis from 1.03 to 27.24 and 1.03 to 30.76, respectively. All medications which listed anosmia within the top AEs had PRR and ROR values exceeding 2 and 1, respectively. The PRR for headache exceeded 2 for 1 medication and the ROR exceeded 1 in 7 medications. Conclusion: The AEs of dyspnea, anosmia, ageusia/dysgeusia, epistaxis, and headache are reported within the FAERS database for commonly prescribed INSs. When compared against the existing scientific literature, the clinical significance of this reporting tool from the FDA for these classes of medications remains unvalidated.